2019
DOI: 10.1111/jocd.12894
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of powdered polydioxanone in terms of collagen production compared with poly‐L‐lactic acid in a murine model

Abstract: Summary Background There are many collagen‐stimulating fillers, including calcium hydroxyapatite, polycaprolactone (PCL), and poly‐L‐lactic acid (PLLA), and other materials have been tested. Polydioxanone (PDO) has recently been used as absorbable thread‐lifting material due to its collagen‐forming effects. PDO in powdered form is expected to be a good material for collagen‐producing fillers. Objectives To evaluate the collagen‐producing effects of powdered PDO injection compared with PLLA injection in a murin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 14 publications
4
25
0
Order By: Relevance
“…The injection of PDO thread acts as a powerful stimulant of collagen formation. The immediate effect of thread insertion is tissue lift due to the mechanical effect[ 3 , 7 ]. Yoon et al [ 7 ] reported that the PDO thread induces fibrous connective tissue formation, an increase in the number of nearby capillary vessels, and a reduction in the thickness of the fat layer due to fat cell denaturation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The injection of PDO thread acts as a powerful stimulant of collagen formation. The immediate effect of thread insertion is tissue lift due to the mechanical effect[ 3 , 7 ]. Yoon et al [ 7 ] reported that the PDO thread induces fibrous connective tissue formation, an increase in the number of nearby capillary vessels, and a reduction in the thickness of the fat layer due to fat cell denaturation.…”
Section: Discussionmentioning
confidence: 99%
“…The immediate effect of thread insertion is tissue lift due to the mechanical effect[ 3 , 7 ]. Yoon et al [ 7 ] reported that the PDO thread induces fibrous connective tissue formation, an increase in the number of nearby capillary vessels, and a reduction in the thickness of the fat layer due to fat cell denaturation. The PDO begins to disassemble after 3 mo of thread insertion and disappears by 6 mo[ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This in lammatory reaction elicits resorption and the formation of ibrous connective tissue about the foreign body, causing dermal ibroplasia that leads to the desired cosmetic effect [2]. Kim et al, 2019 reported that powdered polydioxanone injection induces collagen formation more effectively than PLLA injection [215].…”
Section: Astaxanthinmentioning
confidence: 99%
“…Botelho et al, 2014 nanostructured formulation of progesterone (10%) combined with estriol (0.1%) + estradiol (0.25%) is safe and effective in re-establishing optimal serum levels of estradiol and follicle-stimulating hormone and relieving the symptoms of menopause [223]. Abdi et al, 2017 also concluded that use of transdermal nanoformulations in hormone therapy can relieve climacteric symptoms and prevent other postmenopausal symptoms [226][227][228][229][230][231][232][233][234][235][236][237][238][239][240][241][242][243][244][245].…”
Section: Astaxanthinmentioning
confidence: 99%